Modern Teachers of Ars moriendi - Janiak, Agnieszka (Religions, 2021)
It is evident that a change is happening, a breakthrough, in perceptions of death; the next episode is being unveiled. After the stages Philippe Aries named death of the tame and then death of the wild, people today are finally experiencing the humanizing of death, which we call sharing death, whose influence is worth deep analysis. Our hypothesis is that today, Ars moriendi, meeting the needs of the dying, may be learned from the so-called death teachers, whose message is growing noticeably in society. This research shows a certain reversal of social roles that are worth noting and accepting. In the past, a priest was a guide and a teacher in the face of dying and death; today, he has the opportunity to learn Ars moriendi from contemporary teachers of dying, to imagine an empty chair standing by a dying person.